The inspectorate of education and some unresolved challenges for the improvement of learning, teaching and assessment of the L2 language in secondary education in Andalusia, Spain - Fernández Molero, José Francisco (Avances en Supervisión Educativa, 2019)
For the time being an Education Inspector (2008-nowadays), the author has had so many opportunities of supervising the acquisition of English as a second language (L2) at Secondary Schools in Andalusia, Spain. The recent report conclusions from AGAEVE and ‘Pablo de Olavide’ University (Seville, Spain) on Bilingual Education in Andalusia (AGAEVE/UPO, Francisco Lorenzo, 2019) is brought about together with the author’s point of view as an Education supervisor.  By means of a number of specific proposals, which may also be considered of general interest by Education authorities and Education Inspectorate at the same time, the article now intends to open the debate over what to the author seems to be some unresolved challenges for the improvement of learning, teaching and assessment of the L2 language in Secondary Education in the self-governed community of Andalusia, Spain.
Keywords: Inspectorate of Education; proposals; challenges; improvement; learning; teaching; assessment; L2; english language; plurilingualism; bilingualism